Artificial Muscles Based on Ultra-Small Single-Walled Carbon Nanotubes - Vuong, Van Thanh; Nguyen, Tuan Hung; Do, Van Truong (Old Journal, 2019)
The effects of charge doping on the strain and electronic structure of ultra-small single-walled carbon nanotubes (SWNTs) are investigated by using first principle calculations. The obtained results show that the actuator strain and Fermi energy of the SWNTs are a function of charge doping level. The strain of the (2, 2) SWNT is larger than that of the (3, 3) SWNT at the same doping level due to their very large curvature effect. The strain of the (2, 2) SWNT obtained by charge doping ranging from -2.12% to 1.43%, which shows a candidate for the artificial muscle’s application. In addition, the band structures of the SWNTs at the neutral and charge doping cases are also discussed in this present study.